Magnesium oxide supported nano-gold: a highly active catalyst for solvent-free oxidation of benzyl alcohol to benzaldehyde by TBHP - Choudhary, Vasant R.; Dumbre, Deepa K. (Catalysis Communications, 2009)
Nano-size gold particles deposited on MgO by the homogeneous deposition- precipitation showed very high catalytic activity with nearly 100% conversion of benzyl alcohol in a short reaction period (0.5 h) and more over showed excellent reusability in the process. Influence of the catalyst support (MgO, CaO, BaO, SrO, Al(2)O(3), Ga(2)O(3) and In(2)O(3)), method of gold deposition, Au loading and catalyst calcination temperature and also that of the reaction conditions (viz. reaction time and temperature) on the benzyl alcohol to benzaldehyde oxidation have been thoroughly investigated. (C) 2009 Elsevier B.V. All rights reserved.
Keywords: Alkaline earth oxides; Benzaldehyde; Benzyl alcohol; Gr.IIIa metal oxides; Oxidation